187k views
21 votes
F(-2)for the function f(x)=3x-1

User Soulsabr
by
4.7k points

2 Answers

8 votes

Explanation:

From what I know

3x-1=0

3*(-2)-1=0

-6-1=0

=-7.

I'm not sure but u can try it.

User Artyom Chernetsov
by
4.4k points
9 votes

The value of f(-2) in this function is f(-2) = -7

To solve this expression, just replace 'x' with -2. When the expression is ready, let's calculate it.

First we multiply or divide, then add or subtract.

Resolution

f( x ) = 3x - 1

f(-2) = 3 · (-2) - 1

f(-2) = -6 - 1

f(-2) = -7

So, the alternative value is f(-2) = -7

User Bznein
by
5.1k points